Phosphine‐Catalyzed Chemoselective [4+3] Cycloaddition of Alminine Esters and β′‐acetoxy Allenoates for Divergent Synthesis of Azepines. Issue 3 (3rd December 2019) - Dai, Zonghao; Zhu, Jin; Wang, Jiahua; Su, Wenbo; Yang, Fulai; Zhou, Qingfa
Abstract: Abstract Text. A general method for the synthesis of structural diversity and complexity of azepines from aldimine esters and β′‐acetoxy allenoates is reported. Under phosphine catalysis, a [4+3] cycloaddition for the formation of 1, 3‐dihydro‐2 H ‐azepine‐2, 2, 4‐tricarboxylates was achieved with broad substrate scope under mild reactions. A switchable process was given and a variety of important 2, 3‐dihydrochromeno[4, 3‐b]azepin‐6(1 H )‐ones were selectively formed when the reaction was performed in the presence of Cs2 CO3 and PPh3, which involved an intramolecular ester group migration and subsequent lactonization of 1, 3‐dihydro‐2 H ‐azepine‐2, 2, 4‐tricarboxylates. Besides easy handle process, high synthetic value of resulting products, it is worth to note that this work showed the novel example of 1, 5‐ethoxycarbonyl migration. Abstract :